Cellular and molecular mechanisms of vitamin D in food allergy - Poole, A.; Song, Yong; Brown, H.; Hart, P.; Zhang, Guicheng (2018)
© 2018 Journal of Cellular and Molecular Medicine published by John Wiley & Sons Ltd and Foundation for Cellular and Molecular Medicine. Food allergies are becoming increasingly prevalent, especially in young children. Epidemiological evidence from the past decade suggests a role of vitamin D in food allergy pathogenesis. Links have been made between variations in sunlight exposure, latitude, birth season and vitamin D status with food allergy risk. Despite the heightened interest in vitamin D in food allergies, it remains unclear by which exact mechanism(s) it acts. An understanding of the roles vitamin D plays within the immune system at the cellular and genetic levels, as well as the interplay between the microbiome and vitamin D, will provide insight into the importance of the vitamin in food allergies. Here, we discuss the effect of vitamin D on immune cell maturation, differentiation and function; microbiome; genetic and epigenetic regulation (eg DNA methylation); and how these processes are implicated in food allergies.